Gambaran Dukungan Sosial Keluarga pada Pasien Kanker Serviks (Studi Kasus) di Puskesmas Kecamatan Pematang Jaya - Avila Rafa Lubis; Murisal Murisal; Mardenny Mardenny (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Cervical cancer is one of the chronic diseases that not only impacts the patient’s physical condition, but also affects psychological and social aspects. In these conditions, family social support is an important factor in helping patients undergo the treatment process and improve their quality of life. This study aims to describe the form of family social support for cervical cancer patients at the Pematang Jaya District Health Center. The research uses a descriptive qualitative method with a case study approach. Data collection was carried out through observation, in-depth interviews, and documentation of cervical cancer patients who met the criteria as informants. Data analysis was carried out using an interactive model which included data collection, data reduction, data presentation, and conclusion drawn. The results showed that the family social support that patients received included informational support, reward support, instrumental support, and emotional support. These four forms of support play a significant role in helping patients understand the condition of the disease, reduce anxiety, strengthen psychological resilience, and increase motivation in undergoing treatment. This study confirms that family involvement as the main support system is very necessary and needs to be integrated in family-based health services to improve the welfare of cervical cancer patients.